Early Islet Damage After Direct Exposure of Pig Islets to Blood:Has Humoral Immunity Been Underestimated? (2012)
Currently, islet transplantation as a cell therapeutic option for type 1 diabetes occurs via islet injection into the portal vein. Direct contact between islets and blood is a pathophysiological “provocation” that results in the instant blood-mediated inflammatory reaction (IBMIR) and is associated with early islet loss. However, the nature of the various insults on the islets in the blood stream remains mostly unknown. To gain insight into the mechanisms, we utilized a simplified in vitro model in which islets were exposed to blood in different clinically relevant but increasingly challenging, autologous, allogeneic, and xenogeneic combinations. Irrespective of the blood type and species compatibility, islets triggered blood clotting